Feedback and the use of land for parking - Lehe, Lewis (Journal of Transport and Land Use, 2016)
Land-use patterns are often the result of feedback effects in which one agent's decision both influences and is influenced by urban form. This paper argues that such feedback---of a positive or negative kind---could plausibly arise in the provision of off-street parking. A stylized model is used to illustrate feedback in the case of bundled parking, to note how such feedback may change a neighborhood in the long run and to analyze several policies. A theme is that feedback opens the door to surprising effects that are hard to predict from the status quo.